2013
DOI: 10.1016/j.jss.2012.10.731
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive Iodine Scanning is Not Beneficial but its Use Persists for Euthyroid Patients

Abstract: Background-Radioactive iodine (RAI) scanning is a method of determining the functional status of thyroid nodules. Historically, practitioners thought "cold," or inactive nodules were more likely malignant. However, surgeons now do not find these scans helpful for preoperative management of euthyroid patients. The purpose of this study was to evaluate the utility of RAI scans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Our study also showed that 4.3% of the thyroid scans showed normal results, 2% showed cold nodules, and 4.3% showed autonomous nodules. The physician's inappropriate use of thyroid scans could be a consequence of routine workup for thyroid nodules having become a habit [31].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed that 4.3% of the thyroid scans showed normal results, 2% showed cold nodules, and 4.3% showed autonomous nodules. The physician's inappropriate use of thyroid scans could be a consequence of routine workup for thyroid nodules having become a habit [31].…”
Section: Discussionmentioning
confidence: 99%